SONGS AS LEARNING MEDIA TO IMPROVE GERMAN VERB CONJUGATION MASTERY OF SENIOR HIGH SCHOOL STUDENTS - Mariyanti Pabibak; Sjuul J. Lendo; Johanna Rimbing (SoCul: International Journal of Research in Social Cultural Issues, 2022)
This study is a Classroom Action Research aimed at investigating the use of songs as a learning media to improve high school students' mastery of verb conjugation at SMA Negeri 2 Tondano. This research adopts Kurt Lewin's Classroom Action Research model, which consists of planning, action, observation, and reflection. The study was conducted at SMA Negeri 2 Tondano, specifically in the XI IPS class comprising 15 students. The research was carried out from March to May 2023. The activities were conducted in two cycles over a period of three months. In the first cycle, it was observed that the students were not accustomed to the teaching and learning process that utilized songs as a learning media. This significantly affected the students' level of mastery in verb conjugation for each taught topic. In the second cycle, there was an improvement as both the teacher and students began to familiarize themselves with using songs as a learning media. This was evident from the achievement results, which showed an increase from an average of only 49.9% in the first cycle to 70.8% in the second cycle.